2006
DOI: 10.1002/mmce.20162
|View full text |Cite
|
Sign up to set email alerts
|

Planar electromagnetic bandgap structures

Abstract: This article presents various novel and conventional planar electromagnetic bandgap (EBG)-assisted transmission lines. Both microstrip lines and coplanar waveguides (CPWs) are designed with circular, rectangular, annular, plus-sign and fractal-patterned EBGs and dumbbell-shaped defected ground structure (DGS). The dispersion characteristics and the slow-wave factors of the design are investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…However, these errors can be ignored for the present applications of the slotted ground structures [1-10, 13, 14, 18-20] where their wide stopband and passband are exploited for harmonic suppression and their phase properties as phase sifters. These issues have been addressed in a number of our published works [8,9,13,14]. The discrepancy can also be attributed to the idealness of the calculation blocks and also the fabrication error in the milling machine.…”
Section: Quasi Static Analysis Of Slotted Ground Structurementioning
confidence: 91%
See 1 more Smart Citation
“…However, these errors can be ignored for the present applications of the slotted ground structures [1-10, 13, 14, 18-20] where their wide stopband and passband are exploited for harmonic suppression and their phase properties as phase sifters. These issues have been addressed in a number of our published works [8,9,13,14]. The discrepancy can also be attributed to the idealness of the calculation blocks and also the fabrication error in the milling machine.…”
Section: Quasi Static Analysis Of Slotted Ground Structurementioning
confidence: 91%
“…Since the detailed analyses of DGS were presented in [8,9,13,14], no further analysis of the new five structures reported in the article is presented.…”
Section: Introductionmentioning
confidence: 98%
“…According to the Eqs. (6) and (8), f L increases with the increasing of w. Based on the Eq. (10), it's shown that f H decreases with the increasing of C p .…”
Section: Figurementioning
confidence: 99%
“…Electromagnetic Bandgap (EBG) structures have considerable effects on suppression of the SSN. The coplanar EBG structures possess good performance in low frequency [2][3][4][5][6][7][8][9][10], but the narrow bandwidth makes it cannot achieve the wideband SSN suppression due to the limitations of its own electrical characteristics. The mushroom EBG structure has been embedded between power and ground planes to mitigate the SSN [11][12][13][14], which increases the bandwidth of the stopband, but it decreases low frequency inhibition performance and increases fabrication cost.…”
Section: Introductionmentioning
confidence: 99%
“…These novel and fruitful concepts have given rise to new design approaches that allow us to obtain improved microwave components for upcoming applications. An important research effort was devoted to make these novel periodic structures compatible with planar microwave technologies facilitating their practical implementation and widening significantly the scope of potential usage [6–8]. Specifically, periodic structures of the EBG‐type have been reported as very useful to improve the behavior of planar circuits and antennas by introducing stopbands that forbid the propagation of electromagnetic waves in the unwanted frequency bands and directions.…”
Section: Introductionmentioning
confidence: 99%